Radioecological studies on the drained bed areas of the Chornobyl nuclear power plant cooling pond - A. I. Lypska; V. I. Nikolaev; V. A. Shytiuk; O. O. Burdo; D. O. Vyshnevskyi (Ядерна фізика та енергетика)
The results of radioecological monitoring of the research sites located on the drained areas and the coastal of the ChNPP cooling pond are presented. The features of the spatial distribution of the exposure dose rate, the density of soil radionuclide contamination by the emergency radionuclides were determined. The content of incorporated radionuclides in representatives of the genera Myodes and Sylvaemus were studied, the individual and interspecies variability of 137Cs and 90Sr levels in animals within the limits of one research site was determined. Currently, the indicators of radioactive contamination of biota in the drained areas of the cooling pond are within the variation of those values that are characteristic of most areas of the Chornobyl exclusion zone.